2020
DOI: 10.7554/elife.53930
|View full text |Cite
|
Sign up to set email alerts
|

JMJD6 cleaves MePCE to release positive transcription elongation factor b (P-TEFb) in higher eukaryotes

Abstract: More than 30% of genes in higher eukaryotes are regulated by promoter-proximal pausing of RNA polymerase II (Pol II). Phosphorylation of Pol II CTD by positive transcription elongation factor b (P-TEFb) is a necessary precursor event that enables productive transcription elongation. The exact mechanism on how the sequestered P-TEFb is released from the 7SK snRNP complex and recruited to Pol II CTD remains unknown. In this report, we utilize mouse and human models to reveal methylphosphate capping enzyme (MePCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…super elongation complex is only a docking site for P‐TEFb. Based on our recent results, CTD of Pol II requires the help of BRD4 and JMJD6 to recruit P‐TEFb from the 7SK snRNP complex, 13 or Tat protein in HIV to hijack P‐TEFb 139 . MLL‐fusion alone is unable to recruit P‐TEFb.…”
Section: A Third Underlying the Mechanism Of Mll‐fusions To Trigger Tmentioning
confidence: 97%
See 2 more Smart Citations
“…super elongation complex is only a docking site for P‐TEFb. Based on our recent results, CTD of Pol II requires the help of BRD4 and JMJD6 to recruit P‐TEFb from the 7SK snRNP complex, 13 or Tat protein in HIV to hijack P‐TEFb 139 . MLL‐fusion alone is unable to recruit P‐TEFb.…”
Section: A Third Underlying the Mechanism Of Mll‐fusions To Trigger Tmentioning
confidence: 97%
“…Thus, it is essential to understand how paused Pol II is regulated in higher eukaryotes, which remains elusive to this day. In recent years, we fortuitously found that a group of orphan family members of Jumonji domain containing protein family, including JMJD5, JMJD6, and JMJD7, may work together with the super elongation complex to play critical roles in the release of paused Pol II 10‐13 (Liu et al, unpublished). The pausing of RNA Pol II at promoter regions is a unique transcription regulation mechanism seen in higher eukaryotes 48‐54 .…”
Section: Jmjd5 and Jmjd7 Cleave Arginine Methylate Histone Tails To Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockouts of JMJD6 could lead to severe defects in mice, which suggested critical roles of JMJD6 in development 35 . Furthermore, JMJD6 could accompany with BRD4 to regulate the activity of CDK9 and RNA polymerase II complex 36 . However, the specific function and therapeutic significance of JMJD6 in RCC are indefinite.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to hydroxylate lysine residues and demethylate arginine residues in proteins and histones [ 6 , 7 , 8 , 9 ]. Recently, additional catalytic activities were proposed, namely a kinase and a protease function [ 10 , 11 ]. Among the substrates for JMJD6-hydroxylation activity is the U2AF 65 kDa subunit (U2AF65), a key regulator of splicing [ 6 ].…”
Section: Introductionmentioning
confidence: 99%